Comparative study of cemento-ossifying fibroma and focal cemento-osseous dysplasia in the jaw - 15 year retrospective inquiry and literature review - Jiejing Yin; Yekaterina Belogrivtseva; Ahmed Lazim; Samir Amer; Dina Zenezan; Riya Kuklani; Daniela Proca (Elsevier, 2024)
Background: Cemento-ossifying fibroma (COF) and focal cemento-osseous dysplasia (FCOD) are benign neoplasms occurring in the mandible and maxilla; histologically, they both show normal bone replacement by a fibrous stroma containing variable amounts of calcified fragments resembling bone and cementum. FCOD is relatively common and requires observation; COF is rare and its growth over time can lead to deformity in the head and neck region. Surgical removal of COF at an early stage is critical to prevent recurrence and deformity. Therefore, distinguishing COF from FCOD is important for proper further management. Methods and Materials: To determine the parameters differentiating COF from FCOD, we retrospectively analyzed 15 COF cases and 27 FCOD cases reviewed between 2005 and 2020 at Temple University Hospital. Demographic, radiographic and histopathologic characteristics were compared by using Student's t test for continuous variables and Chi-square test for categorical variables. Results: In the non-histopathologic spectrum, COF occurred at a younger age (average age-31yo versus FCOD 43 yo). FCOD showed female predilection compared with COF. No significant difference was observed regarding location and radiographic density. However, COF was significantly associated with radiographic cortical expansion. In the histopathologic spectrum, FCOD was more frequently associated with significant intralesional hemorrhage, increased vascularity, osteoblastic rimming of trabeculae, and ginger roots -like bone trabeculae. Discussion: We demonstrated 7 clinical, radiographic, and pathologic parameters that can help differentiate COF from FCOD. Comprehensive assessment of the distinguishing characteristics is valuable for accurate diagnosis and treatment of these two entities, aiding in minimizing unnecessary procedures for FCOD and averting facial deformities caused by COF.